The Relationship between Patient Safety Culture and Barriers to Medical Errors Reporting Among Nurses in Tehran Hospitals - Abbas Daneshkohan; Soad Mahfoozpour; Mohammad Palesh; Babak Fazli Ouchhesar; Farasat Fazli Ouchhesar (Kerman University of Medical Sciences, 2020)
The Relationship between Patient Safety Culture and Barriers to Medical Errors Reporting Among Nurses in Tehran Hospitals   Daneshkohan Abbas1, Mahfoozpour Soad2, Palesh Mohammad1, Fazli Ouchhesar Babak3, Fazali Ouchhesar Farasat4* 1. Assistant Professor, Department of Health Services Management, Virtual School of Medical Education and Management, Shahid Beheshti University of Medical Sciences, Tehran, Iran 2. Associate professor, Safety Promotion and Injury Prevention Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran 3. Lecturer, Health Promotion Research Center, Zahedan University of Medical Sciences, Zahedan, Iran 4. MSc in Health Services Management, Shariati Hospital, Tehran, Iran *Corresponding Author: Farasat Fazali Ouchhesar Address: Shariati Hospital, Jalal-e-Al-e-Ahmad Hwy, North Kargar St, Tehran, Iran Tel: 00982184901000                                         Email: farasat.fazli@yahoo.com Abstract: Background & Objectives: According to World Health Organization, patient safety is a serious public health issue, an important aspect of the quality of health care, and a vital prerequisite for universal health coverage. The objective of this study was to investigate nurseschr('39') perceptions of patient safety culture (PSC), barriers to medical error reporting, as well as the relationship between the two. Methods: This descriptive-analytical study was conducted in six public hospitals in Tehran on 420 nurses who were selected using multistage sampling. The Hospital Survey on Patient Safety Culture (HSOPSC) and a researcher-made questionnaire on barriers to medical error reporting were utilized. Data were analyzed using correlation tests, t-test, analysis of variance (ANOVA), and multivariate regression analysis using SPSS software (version 20). Results: The mean score of patient safety culture was 52.01 and the mean score of barriers to error reporting was 3.13. Manager expectations and actions had the highest mean score (69.8) and non-punitive response to errors had the lowest mean score (23.6) among the dimensions of patient safety culture. Fear of the consequences of reporting an error was the most important perceived barrier to error reporting (3.37). There was a significant negative correlation between safety culture and perceived barriers to error reporting (P<0.001). Conclusion: Setting up an anonymous reporting system as well as increasing managerschr('39') support for error reporting and providing positive feedback to nurses are essential steps to improve error reporting.   Keywords: Patient Safety Culture, Error Reporting, Medical Error, Teaching Hospital   Citation: Daneshkohan A, Mahfoozpour S, Palesh M, Fazli Ouchhesar B, Fazali Ouchhesar F. The Relationship between Patient Safety Culture and Barriers to Medical Errors Reporting Among Nurses in Tehran Hospitals. Journal of Health Based Research 2020; 5(4): 435-50. [In Persian]